Ciprofloxacin i.v Defining Its Role in Serious Infections - Garrard, Christopher (Springer Berlin Heidelberg, 1994)
On the occasion of a symposium in Salzburg, an international team of clinicians and pharmacologists presented recent results in profile efficacy, safety and therapeutic use of the antibiotic substance Ciprofloxacin. Of special interest for clinicians will be the clinical outcome in patients with nosocomial pneumonia and other infections of the lower respiratory tract